TRANSFORMASI GELOMBANG DI PANTAI SUKAMARA PROVINSI KALIMANTAN TENGAH - Baharuddin, Baharuddin; Dewi, Ira Puspita (Torani Journal of Fisheries and Marine Science, 2016)
Refraction pattern of waves on the coast Sukamara have been known to conduct research in the year March –April 2014 . The prediction results showed that each season surge wave parameters that form there is adifference. This is because of differences in factors affecting pembangkitkan waves such as wind speed, duration,wind direction, and fetch. I transitional seasons wave direction most of the south and southeast (26.09 %) withheight and wave period at intervals ranging from 2.2 m - 3.1 m and 7.7 s - 8.7 s, the biggest wave of thesouthwest (3.8 m and 9.3 s). East monsoon waves are formed predominantly from the southeast (55.56 %),height and wave period at intervals ranging from 1.7 m - 2.7 m and 6.9 s - 8.1 s. The wave season is from thesouth east which is a storm surge of 3.5 m and 9.0 s. In the second transition back waves varies with thedirection of most of the southeast (26.92%) with height and wave period range in the interval from 1.9 to 3.1 mand 7.2 s - 8,5s. Due to refraction and shoaling pattern, so that the wave will experience changes in height,velocity and wavelength smaller than in the ocean waves. Deflection direction that causes the wave height of thewave decreases due to the speed and wavelength decreases. Convergence (penguncupan waves) generallyoccurs on the contour/coast which juts out (headland) and sund dune area, whereas divergence (spread waves)occur in the contour/coast that juts into the (bay area). Areas experiencing convergence generally cause abreaking wave height greater than the divergence area.Keywords: Sukamara coast, wind direction, wind speed, refraction, konvergen and divergen